Beyond Spiked Honey: Liberation, Eudaimonia, and Social Self-Actualization - Morelock, Jeremiah; Narita, Felipe Ziotti [UNESP] (Springer Nature, 2025)
A cliché tells us that you can catch more flies with honey than with vinegar. This is not always true, or at least not always a simple issue. What constitutes honey? What constitutes “sweetness”? Is revenge sweet? Can you catch flies with revenge? Kindness and positivity, of course, is the idea. Basic simple kindness and positivity are more likely to help you make friends. Clearly, this is an oversimplification, and yet, the American left today could benefit considerably from taking this notion very seriously and maybe taking it not very seriously.